2022-RA-431-ESGO Clinicopathologic features and outcomes of mucinous ovarian tumours: a retrospective study. (20th October 2022) - Katsanevakis, Emmanouil; Addo-Yobo, Waziri; Abu, Jafaru; Nunns, David; Gan, Carmen; Gajjar, Ketankumar
Abstract : Introduction/Background: Mucinous ovarian tumours represent a rare entity of ovarian neoplasms. More specifically some authors report that mucinous ovarian cancer accounts for 12% of ovarian cancer, however newer studies show that the true incidence could be as low as 3%. The aim of this study is to compare and understand the clinicopathological characteristics of patients with mucinous ovarian neoplasms, report the survival rate in patients with mucinous ovarian cancer and show how it may defer according to surgical treatment. Methodology: This is a retrospective data collection on patients with mucinous ovarian tumours (benign, borderline and malignant) operated in Nottingham gynaecological oncology cancer centre over a 5-year period. Data were analysed using SPSS software. The Kolmogorov- Smirnov test was performed to assess the distribution of data and the Kruskal-Wallis test was performed to compare the data across the 3 groups. Results: 245 patients with mucinous ovarian neoplasms were treated in our centre over this period. 26 cases were malignant. The mean age of presentation is 46 years for the benign cases, 52 years for the borderline cases and 54 years for the malignant cases. Mean CA-125 levels in malignant cases is 134 compared to 20 and 35.5 for benign and borderline cases respectively (p<0.01). The overall 5-year survival amongst patients with cancer is 65.4%. The 5-year survival rate amongst adequately debulked patients is 71.4% whereas in the not-adequately debulked cases is 40%. The overall disease recurrence rate is 23% and the average date of recurrence is 8.8 months after primary surgery. Conclusion: Clinical outcomes in adequately debulked cases of mucinous ovarian adenocarcinoma are fairly good, especially in early-stage disease. However, disease recurrence continues to pose challenges to the clinicians. Histological classification of mucinous ovarian neoplasms can also be very challenging, especially in cases of concurrent bowel or peritoneal cancer.